Emotional Intelligence Ability of Leaders as Strategic Decision Makers: An Empirical Study on the Turkish Military - Onay, Meltem; Dinçer, Hasan; Gürsoy, Ali (Afyon Kocatepe Üniversitesi, 2011)
This study aims to determine whether the difference between high-level strategic decision-making staff (Group 2) that are major, lieutenant colonel and colonel and lower-level manager (Group 1) in the Turkish Land Forces according to age and educational background factors in terms of levels of emotional intelligence. Emotional intelligence levels were measured on 213 ranked officers by the Bar¬on Emotional Intelligence Survey. Under the survey results, when the military rank increases, the level of total EI also raises. Thus, a positive relationship between high-level strategic decision making military personnel and total EI is strengthened. Similarly, military origin is observed to have an impact on the level of emotional intelligence as well. Military academy graduates have lower levels of total emotional intelligence compared to officers with other origins.

Bu çalışma, Türk Silahlı Kuvvetlerinde stratejik karar verici olarak ifade edilen binbaşı, yarbay ve albay rütbesindeki üst düzey personel (Grup 2) ile alt kademedeki personel (Grup 1) arasında duygusal zeka düzeyleri açısından yaş ve eğitim durumu değişkenlerine göre farklılık olup olmadığının incelenmesini hedeflemektedir. Duygusal zeka, 213 subaya, Bar-on Duygusal Zeka Testinin uygulanması ile ölçülmüştür. Test sonuçlarına göre, artan rütbe ile toplam duygusal zeka seviyesi artmaktadır. Böylece, stratejik karar veren üst düzey askeri personel ve toplam duygusal zeka arasındaki pozitif ilişki desteklenmektedir. Benzer şekilde, askeri kökenin de, duygusal zeka seviyesi üzerinde etkili olduğu gözlenmektedir. Askeri okul mezunları, farklı kaynaklardan gelen subaylara göre daha düşük duygusal zeka seviyesine sahip olmaktadır.
Keywords: Strategic Decision Making; Emotional Intelligence; Military Leadership